EVALUATING THE ROLE OF GENETIC POLYMORPHISMS AND GENE EXPRESSION OF THE KLK2 GENE WITH THE RISK OF BENIGN PROSTATIC HYPERPLASIA IN IRAQI PATIENTS - Bashar Hamad Motlak; Prof. Dr. Ammar Ahmed Sultan (European Science Publishing, 2024)
Benign prostatic hyperplasia (BPH) is a non-malignant tumor of the prostate that enlarges prostate tissue and reduces the flow of urine from the bladder. Testosterone plays a role in the disease as low testosterone with age leads to hyperplasia of the prostate The present study aimed to evaluate the role of genetic polymorphism and gene expression in the KLK2 gene at the variant locus for rs198972, rs198977, a gene located on chromosome 19 that mainly encodes for enzymes involved in BPH by increasing gene expression for rs198972 and by Fisher's probability (P = 0. 569) between patients and controls. 569) between patients and healthy controls. Homozygous CC and C allele genotypes were considered a causative factor with an odds ratio of 1.43 and 1.43, respectively. The TT and T allele genotypes have a Fisher probability value of P = 0.427, so the TT and T allele genotypes are a protective factor for the disease according to the odds values of 0.45 and 0.70, respectively. In front of heterozygosity and rs198977, the CC and C genotypes have a Fisher probability (P = 0.778) between patients and healthy people. The homozygous CC and C genotype is a protective factor for the disease with a value of Odd ratio of 0.84 and 0.90, respectively. The TT and T allele genotypes had a Fisher's exact probability value of P = 0.666, so the TT and T allele genotypes were considered as an etiologic factor according to the likelihood values of 1.00 and 1.11, respectively. The results of the current study show higher levels of KLK2 gene expression in BPH patients compared to healthy people, as the real time PCR results showed a difference in the CT values between the study groups, and the CT values in patients were lower than the control group, and the folding level in patients (14.35±5.21) was higher than healthy people (1.00±0.00) with statistically significant differences (P<0.001***).
Keywords: KLK2 gene, SNP, Translocation, Odd ratio, Prostatic